Students' Development In Notating The Unit Of Speed - admin admin; Fatimatul Khikmiyah (DIDAKTIKA, 2012)
Students have acquainted with speed from their environment but it is not easy for them to learn the concept of speed since according to Gravemeijer (2007) , the concept of speed is still one of the most difficult quantities. What students learn about speed will be developed when they study at higher education it is very important for teacher to give support for the students so that they are not only able to use the formula deal with the speed but also know the reason behind the formula and how to apply it in other situations. Hence, a series of learning activities which in line with Realistic Mathematics Education (RME) was designed. Design research was chosen as the general heading of the research. It was conducted in SD Al-Fatah(Full day School) in Surabaya-Indonesia with a teacher and 25 students in fifth grade. Research findings show that “paper tapes activity” can lead the students to develop their notion on the unit of speed. Students realise that in order to compare the speed they must be aware of both distance and time as the components of the speed. The function of paper tapes which the students made gradually changing in line with students' thinking process. At the first time, it might only as the path for the toy cars, but then it shows the distance travelled by the car. Finally, students modified those paper tapes as the visualization of the unit of speed which help them to made a table as a strating point to come to the other units of speed.